PENGARUH VARIASI METAL TRANSFER TERHADAP KARAKTERISTIK SAMBUNGAN LAS PADA PROSES PENGELASAN GMAW DENGAN PELINDUNG GAS ARGON - Mansyur Abdul Shaleh; Wijoyo Wijoyo; Rohmadi Rohmadi (Journal of Metallurgical Engineering and Processing Technology, 2023)
This study aims to determine the variation of metal transfer on tensile strength, impact, hardness distribution, macrostructure, microstructure and chemical composition of low carbon steel metal by GMAW welding method. The material used in this study was AISI 1018 low carbon steel. The material was welded using the GMAW method. Variation of globular arc, spray arc and short arc welding. The tests carried out included tensile testing, impact testing, hardness testing, macro-structural observations, micro-structural observations and chemical composition. The test phase to determine tensile strength refers to ASTM E8/E8M-09 with specimen dimensions of 100 mm long, 10 mm wide and 5 mm thick, while for impact testing refers to ASTM E23-07a with dimensions of 55 mm long, 10 mm wide and 10 mm thick. 10 mm with a notch depth of 5 mm and photographic observations of macro, micro and chemical composition. The test results show that the maximum tensile strength with the globular arc welding method is 526.3 MPa and the yield stress is 377.3 MPa, which is greater than that of the low carbon steel parent metal, which is 454 MPa. The impact toughness value of the globular arc welding method is 3.58 J/mm2. Results The microstructure of the weld metal undergoes structural changes in all welding methods. The test results for the chemical composition of the Fe content in low carbon steel materials by welding were 98.78% to 97.76%.